Faktor-Faktor yang Mempengaruhi Perilaku Keselamatan Berkendara : Studi terhadap Kesadaran, Keterampilan, dan Kepatuhan Pengemudi - Anis Hilmi Dwi Syafitri; Suherman Suherman; Irna Hasanah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study aims to identify and analyze the influence of knowledge and awareness on motorcycle riders' safety behavior (safety riding), particularly among online motorcycle taxi drivers. In the context of increasing traffic accidents, understanding the factors influencing riders' compliance with safety regulations is crucial. This research employs a qualitative descriptive method and was conducted from January to April 2025. A total of 15 relevant articles published between 2020 and 2025 were systematically reviewed from credible databases such as Google Scholar, CORE, and ScienceDirect. The analysis reveals that compliance with road safety regulations is influenced by both internal and external factors. Internal factors include the rider’s knowledge level, safety attitudes, age, and riding experience. External factors consist of law enforcement supervision, access to safety training, availability of protective gear, and social support from family and peers. Among these, knowledge and attitude are identified as the most influential aspects affecting safety compliance. Therefore, a comprehensive approach is needed, including continuous education, regular training, and collective awareness-raising to foster a safe riding culture. This study contributes to a better understanding of behavioral aspects related to road safety and serves as a foundation for the development of behavior-based transportation safety strategies